Effect of calcium hypochlorite as an irrigant alternative in the removal of methylene blue after photodynamic therapy under the post-space adhesive interface - Besegato, João Felipe; De Sousa Gomes Costa, Joatan Lucas [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Bravo, Giovanna Righetti [UNESP]; Morais, Jéssika Mayhara Pereira [UNESP]; Escalante-Otárola, Wilfredo Gustavo; Kuga, Milton Carlos [UNESP] (IOP Publishing, 2023)
We evaluated the effect of irrigation protocols in removing methylene blue after photodynamic therapy (PDT) in post-space dentin. Bond strength to dentin and failure mode after fiber post cementation was also evaluated. Ninety bovine teeth were endodontically treated. Post-space preparation and PDT mediated by 0.01% methylene blue and diode laser (660 nm) were performed. Three irrigations protocols were tested (n = 10): distilled water (DW), 2.5% sodium hypochlorite (SH), and 6% calcium hypochlorite (CH). Other specimens were used to investigate the bond strength to post-space dentin according to the irrigation protocol and the post cementation system used (RelyX U200 cement (RU) and GC Gold Label 1 glass ionomer cement (GC) in six groups (n = 10): DW-RU, SH-RU, CH-RU, DW-GC, SH-GC e CH-GC. Regardless of the post-space third, DW showed a lower incidence of residues than SH (p < 0.05), but similar to CH. SH showed similar results to CH (p > 0.05). Regarding the bond strength, CH-RU and CH-GC showed higher values compared to the other groups (p< 0.05), but similar to each other. No differences were observed between the other groups (p > 0.05). Cohesive was the most predominant failure. 6% CH to remove methylene blue after PDT favors the bond strength of RelyX U200 and GC Gold Label.
Keywords: bond strength; fiber post; glass-ionomer cement; methylene blue; photodynamic therapy; self-adhesive cement